2014
DOI: 10.1088/1367-2630/16/5/053018
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-induced dynamic resonance energy transfer

Abstract: In a network of interacting quantum systems, achieving fast coherent energy transfer is a challenging task. While quantum systems are susceptible to a wide range of environmental factors, in many physical settings their interactions with quantized vibrations, or phonons, of a supporting structure are the most prevalent. This leads to noise and decoherence in the network, ultimately impacting the energy-transfer process. In this work, we introduce a novel type of coherent energy-transfer mechanism for quantum s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…Under this hypothesis electronic coherence appear to exhibit lifetimes that can reach the picosecond range thus exceeding expectations from condensed matter systems at least tenfold. This interesting observation gave rise to a variety of attempts for explanations of the long-lived coherences including (i) overall reduction of dephasing [57,83] which are however not compatible with the observed very short lifetimes of optical exciton coherences in the system, (ii) correlations in the noise sources between different sites [52,53,85] which are however not supported by first principles calculations of spectral densities [54][55][56][57] and normal-mode analysis combined with quantum chemical methods [58,59] and (iii) variations of the electronic structure of the FMO complex [86] which are not sufficient however to explain the observed durations. In the following we will show that the inclusion of significant coupling of electronic motion to long-lived vibrational modes [28,34] are capable of explaining the observations [36,37] and even more so to give support to the idea that vibrational motion plays and important role for electronic transport, quantum or classical -a principle which we will show here to be of broader importance in biology.…”
Section: Long-lived Coherences As a Non-equilibrium Processmentioning
confidence: 99%
“…Under this hypothesis electronic coherence appear to exhibit lifetimes that can reach the picosecond range thus exceeding expectations from condensed matter systems at least tenfold. This interesting observation gave rise to a variety of attempts for explanations of the long-lived coherences including (i) overall reduction of dephasing [57,83] which are however not compatible with the observed very short lifetimes of optical exciton coherences in the system, (ii) correlations in the noise sources between different sites [52,53,85] which are however not supported by first principles calculations of spectral densities [54][55][56][57] and normal-mode analysis combined with quantum chemical methods [58,59] and (iii) variations of the electronic structure of the FMO complex [86] which are not sufficient however to explain the observed durations. In the following we will show that the inclusion of significant coupling of electronic motion to long-lived vibrational modes [28,34] are capable of explaining the observations [36,37] and even more so to give support to the idea that vibrational motion plays and important role for electronic transport, quantum or classical -a principle which we will show here to be of broader importance in biology.…”
Section: Long-lived Coherences As a Non-equilibrium Processmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In particular, resonant (or near resonant) interactions between environmental degrees of freedom and those inherent to the system are thought to play an important role in numerous physical processes. [9][10][11][12][13][14][15][16][17][18][19][20] However, a comprehensive picture of such dynamics is only beginning to emerge due to the complexity of the systems in question. Here, by focusing on a proposed model for olfaction as a vibrationally-activated molecular switch, we explore the detailed effects of the environment on the dynamics of electron transfer (ET) in an open quantum system, aiming to gain physical insight into vibrationally-assisted transport processes more generally.…”
Section: Introductionmentioning
confidence: 99%
“…but with an extra field changing Δ G and J DA periodically with time, which originates from the nonequilibrium nature of the vibration. Lim et al have shown that this time‐dependent field can be utilized to control the rate and directionality of EET. The existence of such a field may deviate the conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic effect of multiple underdamped vibrations has also been reported . Furthermore, it has been shown that the nonequilibrium dynamics of these vibrations can generate oscillating beatings in both electronic state populations and coherences, which has also been theoretically proved to be a novel way in controlling the rate and directionality of EET …”
Section: Introductionmentioning
confidence: 93%